Factors promoting development of renal tubulointerstitial lesions in patients with diabetes mellitus - Minara Shamkhalovna Shamkhalova (Endocrinology Research Centre, 2010)
Aim. To identify profibrogenic mediators, markers of endothelial dysfunction and hemostasis in patients with diabetes mellitus (DM) and chronickidney disease (CKD). Materials and methods. The study included 120 patients with DM and 20 age-matched normotensive subjects without DM showing the glomerularfiltration rate (GFR) > 60 ml/min/1.73 m3. Four groups of patients were distinguished: 1 - DM2 patients without renal pathology (n=33), 2 - DM2 patients with diabetic nephropathy (n=24), 3 - DM2 patients with ischemic nephropathy (IN) (n=33) verified by contrast visualization techniques(multispiral CM of abdominal aorta and renal arteries, abdominal angiography of renal arteries or MR angiography of renal arteries and abdominal aorta), 4 - DM1 patients with DN (n=30). Clinical examination included assessment of complaints, analysis of medical history of the main diseaseand concomitant disorders, determination of the main clinical and biochemical characteristics of blood and urine, measurement of НbА1с and 24-hralbuminuria (AU) by standard methods, estimation of GFR by the MDRD formula, ECG, echocardiography, 24-hr AP monitoring, counseling bycardiologist and ophthalmologist (fundal examination by ophthalmoscopy). Standard kits were used to detect profibrogenic mediators and markersof endothelial dysfunction including transforming growth factor-beta (TGF-b), angiotensin II (AT II), monocyte chemoattractant protein (MCP-1),regulated on activation normal T cell expressed and secreted (RANTES), adhesion factors (intracellular adhesion molecule (ICAM-1), vascular celladhesion molecule (VCAM-1) vascular endothelial growth factor (VEGF), interleukin-6 (IL-6), asymmetric dimethylargnine (ADMA), homocysteine(HCYST), metalloproteinases (MMP), von Willebrand factor (vWF), plasminogen activator inhibitor (PAI-I). Results. DM patients with CKD had elevated blood profibrogenic cytokine (MCP-1, TGF-1b, IL-6) and extracellular matrix degradation factor(MMP-9) levels compared with patients without CKD and healthy subjects. These changes were unrelated to the type of diabetes or the cause ofnephropathy, which suggests their contribution to renal pathology through the universal mechanism of tubulointerstitial fibrosis. Activation of profibrogeniccytokines in DM patients with CKD was closely associated with endothelial dysfunction manifest as enhanced production of blood adhesive angiogenic, thrombogenic factors (FW, PAI, VICAM, sICAM, VEGF), and endothelium-affecting factors (ADMA, homocysteine). Mediators of inflammationand fibrogenesis in these patients negatively correlated with GFR and positively with AU, the main markers of renal dysfunction. Hyperuricemia,TGF-1b, ADMA, and MCP-1 are considered to be the risk factors of impaired renal filtration function. Conclusion. The level of profibrogenic cytokines and ndothelial dysfunction factors in DM patients with different renal lesions reflects severity of tubulointerstitialfibrosis. It may be used for the purpose of prognostication and substantiation of intensification of secondary prophylaxis of renal insufficiency.